HOST COMMUNITY AND TERTIARY INSTITUTION STUDENTS’ CONFLICTS IN OGUN STATE: A STUDY OF OLABISI ONABANJO UNIVERSITY AND TAI SOLARIN UNIVERSITY OF EDUCATION HOST COMMUNITIES - SOFADEKAN, Adedayo Oyewole; SALAMI, Nofiu Olamikulehin (EBSU Journal of Social Sciences and Humanities, 2025)
Like in many other states across the country, in Ogun State, conflicts between host community and tertiary institutions students have been a persistent issue, causing violence, property destruction, and loss of life. It is on this premise that this study is undertaken, to examine the host community and tertiary institution student conflicts in Ogun State: A study of OOU and TASUED host communities. The study adopted a desk review method, primarily utilising secondary data sources, and the Intergroup Contact Theory was used as the theoretical framework. The paper reveals that the host community and tertiary institution student conflicts in Ogun State are multi-dimensional, involving factors such as socio-cultural differences, inadequate security infrastructure, poor governance, and communication breakdowns. It also exposed that the absence of effective security personnel can lead to vigilante justice, as seen in the 2023 TASUED conflict, where host community members took matters into their own hands. It revealed that whenever these conflicts erupt they usually disrupt academic activities, damage properties, and result in fatalities or injuries, negatively impacting students’ education and causing immense distress for affected families and communities. It concluded that the experiences of tertiary institutions in Ogun State can provide valuable lessons for other Nigerian and African institutions, emphasising the need to tackle complex issues causing host community and tertiary institution students’ conflicts. It therefore, recommended that the regular dialogue and engagement between the two can help to dispel misconceptions, foster cooperation, and find solutions to shared problems.